2021
DOI: 10.1038/s41467-021-25674-5
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency of intestinal Bmal1 prevents obesity induced by high-fat feeding

Abstract: The role of intestine clock in energy homeostasis remains elusive. Here we show that mice with Bmal1 specifically deleted in the intestine (Bmal1iKO mice) have a normal phenotype on a chow diet. However, on a high-fat diet (HFD), Bmal1iKO mice are protected against development of obesity and related abnormalities such as hyperlipidemia and fatty livers. These metabolic phenotypes are attributed to impaired lipid resynthesis in the intestine and reduced fat secretion. Consistently, wild-type mice fed a HFD duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(33 citation statements)
references
References 55 publications
(81 reference statements)
1
31
1
Order By: Relevance
“…Circulating total cholesterol, high-density lipoprotein (HDL) cholesterol and low-density lipoprotein (LDL) cholesterol concentrations were significantly higher under the Puri-starch regimen compared with Chow during the whole course of the experiment ( Figures 2G–I ). Similar cholesterol levels were observed before in several studies that applied the Puri-starch diet as control condition ( 19 , 23 25 ). Moreover, alanine transaminase (ALT) and aspartate transaminase (AST) were increased after 30 or after 20 and 30 weeks, respectively ( Figures 2M,N ), indicating hepatocyte injury.…”
Section: Resultssupporting
confidence: 87%
“…Circulating total cholesterol, high-density lipoprotein (HDL) cholesterol and low-density lipoprotein (LDL) cholesterol concentrations were significantly higher under the Puri-starch regimen compared with Chow during the whole course of the experiment ( Figures 2G–I ). Similar cholesterol levels were observed before in several studies that applied the Puri-starch diet as control condition ( 19 , 23 25 ). Moreover, alanine transaminase (ALT) and aspartate transaminase (AST) were increased after 30 or after 20 and 30 weeks, respectively ( Figures 2M,N ), indicating hepatocyte injury.…”
Section: Resultssupporting
confidence: 87%
“…This result suggests that while a high amplitude circadian clock is key to protect against the development of numerous diseases and pathologies, a fully functional BMAL1 can also have detrimental effects. In support of this concept, Bmal1 deficiency in the intestine protects against HFD obesity ( 61 ), while its deletion in macrophages improves defense against bacterial infection ( 62 ). Moreover, Bmal1 deletion in myeloid cells attenuates the development of atherosclerosis ( 63 ).…”
Section: Discussionmentioning
confidence: 95%
“…Recent studies revealed that circadian desynchrony was closely related to the disruption of glucose and lipid homeostasis [ 32 , 33 , 34 , 35 , 36 ]. According to Li et al, the misalignment of circadian clock genes could be caused in the lipid accumulation model using HepG2 cells [ 13 ].…”
Section: Resultsmentioning
confidence: 99%